2001
DOI: 10.2136/sssaj2001.6541136x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Characteristics of a Vegetative Buffer Strip Soil and Degradation and Sorption of Metolachlor

Abstract: Numerous studies have documented efficacy of vegetated buffer strips (VBS) in removing herbicides from surface runoff. Little is known about the fate of herbicides after deposition in buffer strip soil. Soil samples (0‐ to 2‐cm depth) were collected from a buffer strip and an adjacent bare field (BF). Soil organic C was two‐fold higher in VBS than in BF, and VBS soil maintained about 0.7 log(10) greater propagule density of total fungi and bacteria and 2 log(10) greater gram‐negative bacteria and fluorescent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
3
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 49 publications
9
77
3
1
Order By: Relevance
“…Pode-se observar que o comportamento apresentado pelo trifluralin foi semelhante ao do S-metolachlor, no qual a dissipação se dá pela combinação da degradação microbiológica e pelo tempo em que o herbicida fica adsorvido ao solo (LeBaron et al, 1988;Pignatello et al, 1991;Accinelli et al, 2001). Trabalhos de campo e laboratório demonstram que a intensidade da dissipação desse herbicida está relacionada à biomassa e atividade microbiana no solo (Staddon et al, 2001;Accinelli et al, 2006); assim, quanto menor a umidade do solo, maior é a supressão da população microbiana.…”
Section: Resultsunclassified
“…Pode-se observar que o comportamento apresentado pelo trifluralin foi semelhante ao do S-metolachlor, no qual a dissipação se dá pela combinação da degradação microbiológica e pelo tempo em que o herbicida fica adsorvido ao solo (LeBaron et al, 1988;Pignatello et al, 1991;Accinelli et al, 2001). Trabalhos de campo e laboratório demonstram que a intensidade da dissipação desse herbicida está relacionada à biomassa e atividade microbiana no solo (Staddon et al, 2001;Accinelli et al, 2006); assim, quanto menor a umidade do solo, maior é a supressão da população microbiana.…”
Section: Resultsunclassified
“…Similar results were observed in VFS systems described above. In VFS areas, a litter layer from decaying above-ground vegetation and a massive network of roots can alter the pattern of organic matter accumulation and consequently, stimulate the microbial population decreasing metolachlor half-life (Staddon et al, 2001).…”
Section: Field Persistencementioning
confidence: 99%
“…TTC, although typically an indicator of microbial respiration (22), did not correlate with any parameter of cyanazine degradation, except for nonextractable 14 C at day 28. Blumhorst and Weber (16) suggested that formation of cyanazine amide and acid under neutral conditions was likely due to microbial activity.…”
Section: Discussionmentioning
confidence: 86%
“…Soil texture was ascertained using the hydrometer method. Microbial metabolic activity of field moist soil was estimated using triphenyl-tetrazolium chloride (TTC) dehydrogenase activity as described elsewhere (22).…”
Section: Study Site and Sample Preparationmentioning
confidence: 99%